2013
DOI: 10.3329/pa.v20i1-2.16862
|View full text |Cite
|
Sign up to set email alerts
|

Growth Performance of Larvae Produced from Vitamin E Treated Female <i>Clarias batrachus</i> (Linnaeus)

Abstract: An experiment to observe the growth performance of the larvae produced from female Clarias batrachus treated with 4 dietary levels of vitamin E viz. 0 mg, 50 mg, 100 mg, and 200 mg /kg feed was conducted for 28 days. After rearing for 3 months females were used for induction of breeding to produce larvae. Same dose of pituitary gland (100 mg PG/kg body weight) was used for all treatments. From the 7 th day of hatching, the larvae were reared for another period of 28 days to see growth and survival rate of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 3 publications
(2 reference statements)
1
1
0
Order By: Relevance
“…Similar results were observed by Mollah et al (2009) where the larvae of Clarias batrachus produced from female broods fed with 100mg vitamin E/kg feed performed better compared to other feeding doses. King et al (1985) observed that the use of vitamin E in the diet of rainbow trout (Salmo gairdneri) had a significant effect on the final levels of α-tocopherol in eggs than fish deprived vitamin E. They further added that during egg development, α-tocopherol slowly but efficiently transferred from the yolk to the developing embryo and the mortalities during egg development were inversely related to α-tocopherol content of the eggs.…”
Section: Resultssupporting
confidence: 76%
“…Similar results were observed by Mollah et al (2009) where the larvae of Clarias batrachus produced from female broods fed with 100mg vitamin E/kg feed performed better compared to other feeding doses. King et al (1985) observed that the use of vitamin E in the diet of rainbow trout (Salmo gairdneri) had a significant effect on the final levels of α-tocopherol in eggs than fish deprived vitamin E. They further added that during egg development, α-tocopherol slowly but efficiently transferred from the yolk to the developing embryo and the mortalities during egg development were inversely related to α-tocopherol content of the eggs.…”
Section: Resultssupporting
confidence: 76%
“…All facilities including water supply, inlet and outlet were provided. A distinct feed rich in protein and vitamin-E, were provided at those 4 months which enhances the gonadal maturation in fishes (Mollah et al, 2009). Feed was applied at 5% of their body weight twice a day during the whole 10 months period.…”
Section: Improved Nursery and Grow-out Management Of Minnow In Earthen Pondsmentioning
confidence: 99%